ANALISIS PENGAMBILAN KEPUTUSAN DALAM KENDALA DI UMKM MUTIARA BERAS - Alya Ramadhani; Aqsa Muhardsyah; Gunawan Detia Rahman; Komariah, Komariah; Ujang Suherman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the decision-making process carried out by Mutiara Beras MSME actors in facing various business constraints. The focus of the study is on labor management, capital, raw materials, and marketing. The research method used is a qualitative approach with data collection techniques through observation and direct interviews with business owners. The results show that decision-making at Mutiara Beras SMEs has been able to maintain business operational stability, especially in terms of labor and capital, which have not experienced any significant obstacles. However, obstacles were still found in the management of certain raw materials, particularly subsidized cooking oil, as well as in marketing, because the store is still relatively new and the use of social media has not been optimized. These findings indicate that decision-making is adaptive to field conditions, but long-term planning still needs to be strengthened so that the business can develop sustainably